ESTRUCTURA MUSCULAR FEMORAL DE XEROMELISSINAE (HYMENOPTERA, COLLETIDAE) - Toro, Haroldo; Magunacelaya, J. C. (Acta Entomológica Chilena, 2022)
Chüicola (Chüicola) rubriventris; Ch. (Oediscelis) vemalis; Ch. (Stenoediscelis) inermis; Ch. (Idioprosopis) chalcidiformis; Chilimelissa luisa; Xenochilicola mamigna y Xeromelissa wümattae. In all the species with enlarged femora, the flexor muscle is highly enlarged and inserted dorsally in the basitibial area; the extensor muscle is not modified. The enlargement of the tibia is not related to the tarsal muscle size. The tibial muscles of the females and the males with not enlarged posterior femora are unmodified. Neofidelia prófuga (Fideliidae) and Leucospis hopei (Leucospidae) are similar, when compared with Xeromelissinae, but the shape of the tibia and other characters point out a different function. The enlarged femora of Pararhophites orobinis (Anthophoridae), shows a larger extensor muscle. The presence of grasping structures in the posterior región of the males of Xeromelissinae suggest a role in mating.